The Czech and Slovak republics : twenty years of independence, 1993-2013 - Stolarik, M. Mark, 1943- (Central European University Press, 2016)
"This manuscript consists of ten chapters, two by former Prime Ministers of the Czech and Slovak Republics (Petr Pithart and Jozef Moravcik), plus eight leading scholars (four Czechs: Jan Rychlik, Adela Gjuricova, Martin Pospisil and Oldrich Tuma; and four Slovaks: Jozef Zatkuliak, Juraj Hocman, Martin Butora and Miroslav Londak) and eight knowledgeable commentators from North America (Carol Skalink Leff, James W. Peterson, John Gould, Kevin Deegan-Krause, Michael Kraus, Sharon Fisher, Sharon Wolchik, and Stanislav J. Kirschbaum). The chapters and commentaries put forward a comparison of the Czech and Slovak Republics over the past twenty years. They deal with the causes of the breakup of Czechoslovakia in 1993 and the political developments, the economic developments and the social developments in the new republics. This is the only English-language manuscript that presents the findings of the leading Czech and Slovak, and North American, scholars in the field. It brings new insights into the breakup of Czechoslovakia and into subsequent political, economic and social developments in those countries. The most significant finding of all the scholars was that, in spite of predictions by various pundits in the Western World that the Czech Republic would flourish after the breakup and Slovakia would languish, the opposite has happened. While the Czech Republic did well in its early years, it is now languishing while the Slovak Republic, which had a rough start, is now doing very well. Anyone interested in the history of the Czech and Slovak Republics over the last twenty years will be very interested in reading this book"--Provided by publisher